Modifiable risk factors for young onset dementia. Issue 2 (March 2019) - Cations, Monica; Withall, Adrienne; Draper, Brian
Abstract : Purpose of review: Although young onset dementia (YOD) causes high levels of burden and distress, factors that contribute to its onset are not well understood. Identifying relevant modifiable risk and protective factors for YOD can inform efforts to prevent or delay onset of symptoms to later in life. Recent findings: Studies of modifiable factors for YOD have increased in frequency in recent years. Poor educational attainment and low socioeconomic status, a history of heavy alcohol use, and poor cardiovascular health may be key targets for YOD prevention or delay. Traumatic brain injury has attracted significant attention but evidence of its importance is limited except in cases occurring secondarily to the injury. Summary: A growing body of evidence suggests that modifiable risk factors have a role in modulating the age of dementia onset. Clinicians should be aware that many people with YOD will present with complex histories of multifactorial (including modifiable and nonmodifiable) risk exposure. Exploring trajectories of risk and gene–environment interactions is an important future research direction and will inform targeted prevention efforts.